The Impact of Financing and Business Assistance on the Business Income of Islamic Bank Clients - Mochammad Aldiyansyah; Nasrulloh (Management Analysis Journal, 2024)
This study aims to determine the impact of financing and business assistance provided by Islamic banks on client business income, so that it can help clients to get better income. Achieving this goal is important to evaluate the effectiveness of financing products and Islamic bank assistance programs so that they can support the development of MSMEs, help increase client income so that they are able to complete transactions with Islamic banks more quickly, and encourage the optimization of the role of Islamic banks in empowering the community's economy according to the principles of Islamic finance. This research is a type of quantitative research in which the impact between variables will be discussed. The sample in this study amounted to 48 Islamic bank clients who were determined based on the research criteria. The data that has been collected will be processed using the SPSS v. 27 statistical tool to conduct the validity and reliability test, then classical assumption test, followed by the F-test, T-test, multiple regression analysis, and coefficient of determination (R²).  The results of this study indicate that financing and business assistance have a significant impact of 68.7% on the business income of Islamic bank clients. This shows that if financing and business assistance continue to be given to clients, the clients opportunity to get a better income will be wide open and the client will be able to immediately pay the rest of the loan on time